Noise level during COVID-19 state of emergency in avenida Brasil, Lima – Peru - Rodriguez Flores, Ruben Gilberto (2022)
Considering what is pertinent to the fact that the allocation of credits is the main After the World Health Organization established the condition of pandemic by COVID-19, the different countries established various restrictions to deal with the disease, in this context the government of Peru issued the Declaration of the State of Sanitary Emergency as well as the regulation of the conditions of Compulsory Social Immobilization that restricted the development of various commercial activities, the objective of the study was to analyze and evaluate the effects of the restrictive measures on vehicular flow and noise levels on Avenida Brasil, one of the most important roads in the city of Lima. The study lasted five months and its beginning coincided with the beginning of the first social immobilization, during this period the equivalent noise levels did not exceed the Environmental Quality Standards (ECAs) both during the day (70 dBA) and at night (60 dBA), establishing a Leq-daytime of 66.2 ± 3.7 dBA and a Leq-nighttime of 57.9 ± 1.6 dBA. At the end of the period, the noise level manages to exceed the ECAs, registering a Leq-daytime of 71.6 dBA and a Leq-nighttime Leq of 63.5 dBA, for its part, the vehicular flow at rush hour (07:00-08:00 h) was reduced to 495 v/h on the first day of immobilization to end up registering 655 v/h at the end of the study